The lake house [videorecording (DVD)] - Agresti, Alejandro, 1961-; Reeves, Keanu; Bullock, Sandra; Walsh, Dylan (Warner Home Video, 2006)
A lonely doctor who once occupied an unusual lakeside home begins exchanging love letters with its newest resident, a frustrated architect. When they discover that they're living two years apart, they try to unravel the mystery behind their extraordinary romance before it's too late.